Multiple rather than specific autoantibodies were identified in irritable bowel syndrome with HuProt™ proteome microarray - Fan, Wenjuan; Fang, Xiucai; Hu, Chaojun; Fei, Guijun; Xiao, Qiyun; Li, Yongzhe; Li, Xiaoqing; Wood, Jackie D.; Zhang, Xuan (Frontiers in Physiology, 2022)
Immune activation and several autoantibodies might be involved in the pathophysiology of irritable bowel syndrome (IBS). We aimed to identify serum biomarkers for IBS by HuProtTM microarray. IBS patients met Rome III criteria were enrolled. Control groups included healthy controls (HCs) and disease controls (DCs). In stage I, we profiled sera from IBS and control groups with HuProtTM microarrays. Based on significant different proteins in stage I, IBS focused microarrays were constructed and validated in a larger cohort in stage II, then decision tree models were generated to establish a combination of biomarkers. In stage III, 4 purified proteins were verified by ELISA. Finally, we analyzed the correlation of autoantibodies with symptoms. In stage I, we identified 47 significant different proteins including 8 autoantibodies of IgG, 2 of IgA between IBS and HCs; 13 autoantibodies of IgG, 13 of IgA between IBS and DCs. In stage II, we found the positive rates of 14 IgG and IgA autoantibodies in IBS were significantly higher than HCs. Five autoantibodies of IgG and 7 IgA were comprehensively involved in differentiating IBS and HCs with the sensitivity and specificity to diagnose IBS as 40%-46.7% and 79.4%-86.3%. The median optical density value of ELAVL4 (IgG) and PIGP (IgA) were significantly higher in IBS than HCs. Parts of autoantibodies above were related to IBS symptoms. We found a combination of autoantibodies to differentiate IBS with HCs, but no specific autoantibodies could serve as serum biomarkers for IBS.